Iceland, an Open-Air Museum for Geoheritage and Earth Science Communication Purposes - Federico Pasquaré Mariotto; Fabio Luca Bonali; Corrado Venturini (Resources, 2020)
Iceland is one of the most recognizable and iconic places on Earth, offering an unparalleled chance to admire the most powerful natural phenomena related to the combination of geodynamic, tectonic and magmatic forces, such as active rifting, volcanic eruptions and subvolcanic intrusions. We have identified and selected 25 geosites from the Snæfellsnes Peninsula and the Northern Volcanic Zone, areas where most of the above phenomena can be admired as they unfold before the viewers’ eyes. We have qualitatively assessed the selected volcano–tectonic geosites by applying a set of criteria derived from previous studies and illustrated them through field photographs, unmanned aerial vehicle (UAV)-captured images and 3-D models. Finally, we have discussed and compared the different options and advantages provided by such visualization techniques and proposed a novel, cutting-edge approach to geoheritage promotion and popularization, based on interactive, navigable Virtual Outcrops made available online.